Facilitators and Barriers of Breastfeeding in Post-emergency Settlements: Qualitative Findings From Uganda. (7th June 2021) - Walters, Christine; Rakotomanana, Hasina; Komakech, Joel; Stoecker, Barbara
Abstract: Objectives: Suboptimal breastfeeding practices have been reported among vulnerable populations including those living in post-emergency refugee settlements. This study investigated the barriers and facilitators of breastfeeding in post-emergency settlements in Adjumani district, in the West Nile region in Uganda. Methods: Participants included mothers and fathers of children less than 23 months of age who lived in post-emergency refugee settlements of Agojo, Ayilo, and Nyumanzi. Participants formed a total of five focus group discussions (FGDs); four FGDs for mothers and two FGDs for fathers. The FGDs were conducted in native languages, Dinka and Madi, and were audio-recorded. Data were transcribed verbatim and back-translated into English. Thematic analysis was used and data were analyzed using NVivo v. 12. Results: The mean age (years) for mothers was 27.1 and 39.7 for fathers. Over half (61.9%) of mothers and many fathers (74.9%) received some formal education. Over a quarter (28.5%) of mothers attended less than 4 antenatal visits during their last pregnancy. Facilitators of breastfeeding included knowledge of breastfeeding benefits, support from husband/father, support from the community, and support from non-governmental organizations. Mothers and fathers reported that breastfeeding protected children from diseases and breasted children grow well. Four themes were identified as barriers of breastfeeding: physical, socioeconomic, knowledge, and psychosocial barriers. Mothers and fathers reported physical barriers such as mothers stop breastfeeding when they are sick or they feel they are not producing enough breastmilk. Mothers described socioeconomic barriers including working outside the home and educated mothers chose to use other milk. Fathers reported psychosocial barriers such as mothers' fear of pain during breastfeeding and maternal mental health issues. Conclusions: Policies and interventions that aim to improve breastfeeding in post-emergency settlements should consider addressing the barriers to breastfeeding at each level: physical, socioeconomic, knowledge, and psychosocial. Involving and encouraging support from husbands/fathers, relatives, and the community may increase adherence to breastfeeding recommendations. Funding Sources: Thoma Chair, Oklahoma State University.